2013
DOI: 10.1124/mol.112.084392
|View full text |Cite
|
Sign up to set email alerts
|

Formation, Reactivity, and Antiplatelet Activity of Mixed Disulfide Conjugates of Clopidogrel

Abstract: In this work, we investigated the formation, reactivity, and antiplatelet activity of various mixed disulfide conjugates of clopidogrel. Our results showed that the production of the active metabolite (AM) from 2-oxoclopidogrel by human liver microsomes (HLMs) is greatly affected by the thiol reductants used. Among the 10 thiol compounds tested, glutathione (GSH) is most efficient in producing the AM at a rate of 167 pmoles AM/ min/mg HLM. Interestingly, no AM but only the mixed disulfide conjugates were forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(45 citation statements)
references
References 26 publications
6
39
0
Order By: Relevance
“…29 This was also in complete agreement with the almost identical results previously described for the formation of both cis 5a and trans 5a′ upon microsomal metabolism of 1a or 2a in the presence of GSH, NAC, or ME, 1,6,19,22 and the exclusive formation of 5a in the presence of ascorbic acid instead of GSH. 11,19 Replacement of GSH with the reductant Tris(carboxyethyl)-phosphine (TCEP) led to the exclusive formation of the cis diastereomers 5b (Figure 3E), as when ascorbic acid was used instead of GSH. This result is in agreement with literature data showing that sulfenic acids are efficiently reduced by TCEP with the formation of the corresponding thiols.…”
Section: ■ Introductionsupporting
confidence: 92%
“…29 This was also in complete agreement with the almost identical results previously described for the formation of both cis 5a and trans 5a′ upon microsomal metabolism of 1a or 2a in the presence of GSH, NAC, or ME, 1,6,19,22 and the exclusive formation of 5a in the presence of ascorbic acid instead of GSH. 11,19 Replacement of GSH with the reductant Tris(carboxyethyl)-phosphine (TCEP) led to the exclusive formation of the cis diastereomers 5b (Figure 3E), as when ascorbic acid was used instead of GSH. This result is in agreement with literature data showing that sulfenic acids are efficiently reduced by TCEP with the formation of the corresponding thiols.…”
Section: ■ Introductionsupporting
confidence: 92%
“…The rapid decrease in ClopNPT and simultaneous increase in the active metabolite in the plasma indicate that oral ClopNPT is rapidly absorbed in the small intestine and subsequently converted to the active metabolite. Although the exact mechanism by which ClopNPT is converted to the active metabolite in vivo remains to be elucidated, it is likely that ClopNPT is converted to the active metabolite by a thiol disulfide exchange reaction with glutathione (Zhang et al, 2013). This exchange may also be accelerated by glutaredoxin and thioredoxin (Hagihara et al, 2011(Hagihara et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, further improvement of the pharmacokinetic (PK)/pharmacodynamic (PD) properties of clopidogrel would provide more efficacious DAPT. We previously reported that ClopNPT, a mixed disulfide conjugate of the active metabolite with 3-nitropyridine-2-thiol (NPT), is readily converted to the active metabolite in the presence of glutathione through a thiol disulfide exchange reaction (Zhang et al, 2013;Scheme 1B). Furthermore, ClopNPT inhibits platelet aggregation in the platelet-rich plasma (PRP) of rabbits upon intravenous administration and its inhibitory effects do not require bioactivation by P450s .…”
Section: Introductionmentioning
confidence: 99%
“…Thiolactone 2 (a 1:1 mixture of 2a and 2b) was incubated for 15 minutes at 37°C with HLMs in the presence of NADPH and GSH (5 mM) to reduce sulfenic acid 4 to the corresponding thiols (H1-H4) (Dansette et al, 2009(Dansette et al, , 2010Zhang et al, 2013). A UPLC-Q/TOF MS study of the incubate showed the formation of four thiol isomers exhibiting a molecular ion (ESI + ) corresponding to [M + H] + that was characterized by two peaks at m/z = 356.073 and 358.071 with the ratio expected for the 35 Cl and 37 Cl isotopes.…”
Section: Chiral Stability Of Thiolactone 2 Isomers (2a and 2b) In Bufmentioning
confidence: 99%
“…The sulfenic acid 4 is highly unstable and can be rapidly reduced by glutathione (GSH) to form a mixed disulfide conjugate 5, which is subsequently reduced by another GSH molecule to form the active thiol 6 (Fig. 1) (Dansette et al, 2009;Zhang et al, 2012Zhang et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%